Microbiological profile of urinary tract infection in patients with burn injuries - Kundu, Rajib; Das, Swapan; Chattopadhyay, Bani P. (International Surgery Journal, 2021)
Background: As per WHO around 1,95,000 people died every year due to burn injuries. After initial 72 hours, Infections are the most common cause of death in patients with burn injuries and urinary tract infection was second most commonly reported infectious complication. This study was tried to determine the pattern of microorganisms responsible for urinary tract infection. Methods: After matching inclusion and exclusion criteria, total 55 patients were taken for this institution based prospective observational study. Samples were collected on day 7 and cultured aerobically in MacConkey agar and 5% blood agar and antibiotic susceptibility testing was done on Muller Hinton agar using Kirby-Bauer disc diffusion method. Results: 29.1% samples were positive for microorganisms, of which Escherichia coli was most common isolated organism, it is found in 18.2 % of study population. nitrofurantoin was found to be most effective antibiotic against Escherichia coli. Conclusions: Gram-negative cocci were most prevalent organisms, causing urinary tract infection in patients with burn injuries. Escherichia coli was most common isolated organism and nitrofurantoin was most effective against it. Overall piperacillin/tazobactam has height sensitivity.